Factors associated with fetal karyotype in spontaneous abortion: a case-case study - Qinghua Xu; Ying Chan; Yun Feng; Baosheng Zhu; Bicheng Yang; Shu Zhu; Lingyun Su; Li Zou; Na Feng; Yan Li (BMC, 2022)
Abstract Background Most embryos that spontaneously abort during early pregnancy are found to have chromosomal abnormalities. The purpose of this study is to explore the factors involved in chromosome aberrations during embryogenesis. Methods A case-case study was performed to compare the risk factors for spontaneous abortion with and without embryo chromosome aberration. A total of 160 cases of spontaneous abortion were enrolled from a tertiary general hospital in Kunming. KaryoLite BACs-on-Beads (KL-BoBs) and fluorescence in situ hybridization (FISH) were employed to determine chromosomal constitution of abortion chorion villus samples. Maternal serum levels of homocysteine (Hcy) were detected by high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Information about clinical background and environmental exposure was collected through a self-designed questionnaire. To identify the inherited chromosomal abnormalities, couples with chromosomal abnormalities in abortus were recalled for karyotyping. Results The overall rate of chromosomal abnormalities was 62.5% (100/160, KL-BoBs combined with FISH) including 51.9% (83/160) aneuploidies, 6.3% (10/160) polyploidies, and 4.4% (7/160) structural abnormalities. Only one case of structural abnormality was found to be inherited from maternal balanced translocation. Compared to abortus with normal karyotype, abortus with abnormal karyotype showed a positive association with parental age and elevated maternal serum homocysteine (Hcy) level, but negative association with previous miscarriage and perceived noise. Conclusions Embryonic chromosomal aberrations accounted for the majority of spontaneous abortion cases. A combination of internal and external factors may induce spontaneous abortion through fetal chromosomal aberrations or other pathogenic mechanisms.